Bible and mission : Christian witness in a postmodern world - Bauckham, Richard; Bauckham, Richard (Grand Rapids, MI. Baker Academic. UK. Paternoster Press., 2003)
This engaging study provides a new way of looking at Scripture--one that takes seriously the biblical idea of mission. Richard Bauckham shows how God identifies himself with particular individuals or people in human history in order to be known by all. He is the God of Abraham, Israel, and David and, finally, the one who acts through Jesus Christ.
Bauckham applies these insights to the contemporary scene, encouraging those involved in mission to be sensitive to postmodern concerns about globalization while at the same time emphasizing the uniqueness of Christian faith. In doing so, he demonstrates the diversity of Christian faith around the world. This book will be rewarding reading for pastors, lay readers, and students of Scripture, mission, and postmodernism.
A hermeneutic for the kingdom of God -- From the one to the many -- Geography : sacred and symbolic -- Witness to the truth in a postmodern and globalized world.
"Easneye Lectures."
"Frumentius Lectures."
Includes bibliographical references.
Keywords: Missions -- Biblical teaching